Cybercrime di Indonesia, Analisis Kriminologi terhadap Ancaman Kejahatan Digital - Neneng Pratiwi Zahra; Bima Guntara (Social Science Academic, 2026)
The development of information and communication technology has spurred digital transformation in Indonesia, but it has also increased various forms of cybercrime that threaten the security of individuals, businesses, and the state. This study aims to analyze cybercrime in Indonesia from a criminological perspective by identifying the causative factors, the characteristics of the crime, and efforts to counter it. The research uses normative legal methods, including a statutory and conceptual approach. Data were obtained through literature studies of laws and regulations, books, scientific articles, and reports from related institutions, and were analyzed qualitatively and descriptively. The results of the study show that the increase in cybercrime is influenced by technological advances, high internet usage, low digital literacy, weak personal data protection, and opportunities for anonymity in cyberspace. The most dominant forms of crime include online fraud, personal data theft, hacking, malware spread, and ransomware. From a criminological perspective, digital crime is shaped by interactions among perpetrators, victims, and the digital environment, which provides opportunities to commit crimes with relatively low risk. Therefore, countering cybercrime requires a comprehensive approach that strengthens regulations, enhances law enforcement, increases digital literacy, strengthens cybersecurity systems, and fosters collaboration among the government, law enforcement officials, the private sector, and the community to create a safe and sustainable digital ecosystem.